Politeness Speech Acts in the Speech of Children: Pragmatic Mistakes and Acquisition - Kavaliauskaitė-Vilkinienė, Viktorija (Taikomoji kalbotyra, 2019)
The paper aims to discuss the expression and development of politeness speech acts, i.e. greeting, saying goodbye, thanking, usage of the word please, apology, congratulation and wishes,  in the speech of a Lithuanian boy, aged 1;6–2;7, and a girl, aged 1;8–2;8. The source of data contains two corpora of transcribed conversations of the children mostly interacting with their mothers (about 20 and 27 hours of recordings are transcribed). The corpora are developed by scholars of Vytautas Magnus University, Lithuania. One of the foci of analysis is to discuss the expression and development of the above-mentioned politeness speech acts and common pragmatic errors regarding the usage of politeness formulas in the children’s speech. Another focus is the investigation of the socialization strategies applied by the parents. Based on the current research by different scholars, the article raises the hypothesis that Lithuanian children in the second or third year of life acquire the majority of politeness speech acts as discussed in this paper.The analysis revealed that at the beginning of the observation children lacked communicative competence to use politeness speech acts in a pragmatically appropriate way. They confused situations when to use politeness formulas of thanking, apology and the word please and lacked the knowledge of how to use politeness adjacency pairs. The study also shows that the repetition of parents’ politeness formulas was common. Furthermore, the appropriate use of spontaneous and pragmatic greeting and saying goodbye was observed first, and only later the usage of thanking and the word please appeared.  However, only few examples of other politeness speech acts (i.e. apology, congratulation and wishes) were observed in the corpus. Therefore, further research is necessary.The results demonstrate that at the beginning of the third year the children used most of the politeness speech acts appropriately. An early acquisition was affected by children’s familiarisation with politeness routines taught by their parents. The parents directed and prompted their children to repeat politeness formulas, elicited them by questions or performatives and sometimes taught children to be polite by producing metalinguistic comments. Current research seems to indicate that other Lithuanian children could demonstrate similar developmental patterns of politeness speech acts and make similar pragmatic errors as well as being similarly socialized to use politeness formulas.
Keywords: psycholinguistics; children’s speech; speech acts; language acquisition; socialization into politeness